PENGARUH BRAND POSITIONING DAN BIAYA WARALABA (FRANCHISE FEE) TERHADAP PEMBELIAN WARALABA (FRANCHISE PURCHASE) PADA USAHA MINUMAN “SEGARA” (Studi di Kota Semarang dan Kabupaten Kendal) - Rendy Ramanda; Yoestini Yoestini (Diponegoro Journal of Management, 2023)
ABSTRACT Competitive advantage in the franchise business can increase the interest of franchisees because it is considered to have a stable market, good reputation, and an established business. The franchisee's decision to purchase a franchise is based on what they value as providing benefits such as profit, and business continuity. This study aims to examine the effect of brand positioning and franchise fees on franchise purchases. This study uses a survey method and is distributed to the franchisee "Segara" with a total of 27 people, and analyzed using multiple linear regression. Based on the results of research, brand positioning partially affects franchise purchases with a comparison of thitung 4.366 > ttabel 2.063 and sig. 0.000 < 0.05 (Alpha), and also the franchise fee (franchise fee) partially affects the purchase of a franchise with a comparison of the value of thitung 2.218 > ttabel 2.063 and sig. 0.036 < 0.05 (Alpha), besides that brand positioning and franchise fees (franchise fees) simultaneously affect the purchase of franchises with a comparison of fhitung 27.656 > ftabel 3.39 and sig. 0.000 < 0.05 (Alpha). The dependent variable can be explained by 69.7% based on the R Square value of 0.697.